2022
DOI: 10.1155/2022/7746144
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Usage in Smallholder Poultry Production in Nigeria

Abstract: The indiscriminate use of antimicrobials in livestock production is of increasing concern due to the threat of antimicrobial resistance in both humans and animals. Much emphasis has been placed on intensively managed poultry production systems, which routinely use antimicrobials as against smallholder poultry production systems (SPPS). Therefore, this study investigated the use of antimicrobials among smallholder poultry farmers in Nigeria, and compared the prevalence of antimicrobial drug use against the prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The increased use of oxytetracycline in poultry could be due to its activity against several bacteria and the cost/effectiveness ratio which attracts most farmers to purchase it [ 88 ]. This is a growing concern with high resistance rates to tetracyclines reported across countries [ 1 , 10 , 26 , 89 , 90 , 91 , 92 ]. However, different from some studies conducted in Bangladesh and France in which the most dispensed antibiotics were fluoroquinolones followed by tetracyclines [ 73 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased use of oxytetracycline in poultry could be due to its activity against several bacteria and the cost/effectiveness ratio which attracts most farmers to purchase it [ 88 ]. This is a growing concern with high resistance rates to tetracyclines reported across countries [ 1 , 10 , 26 , 89 , 90 , 91 , 92 ]. However, different from some studies conducted in Bangladesh and France in which the most dispensed antibiotics were fluoroquinolones followed by tetracyclines [ 73 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been an increase in the use of antibiotics in poultry farming for improved egg production and growth promotion, as well as the prevention and treatment of infections across countries arising from increased intensification of farming [ 1 , 2 , 3 , 4 , 5 ]. This increase in antibiotic use (ABU) in poultry production has been due to an increased global demand for chicken meat and eggs in recent years [ 6 ], with over 119 billion tonnes of chicken meat produced in 2019 and 121 billion tonnes being produced in 2022, with production expected to rise [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high resistance to sulfonamides may be due to the misuse and overuse of this group of antibiotics by farmers. Several studies have reported the predominant use of co-trimoxazole (sulfamethoxazole-trimethoprim) and sulfaquinoxaline in poultry farms in Nigeria [ 26 , 41 , 53 , 69 ]. According to Bamidele et al [ 26 ], sulfonamides are ranked third on the list of antibiotics commonly used in smallholder poultry production systems in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…The lower risk of AMR can be attributed to the unique characteristics of the SPPS which relies on ethnoveterinary practices for therapeutic and non-therapeutic animal care purposes [ 22 , 23 ]. However, the introduction of improved chicken genetics as a developmental program for improving SPPS [ 24 , 25 ] has contributed to a decline in farmers’ use of ethnoveterinary medicine and an increase in the indiscriminate use of antibiotics [ 26 ]. This intervention, though with positive developmental outcomes (food security, livelihoods) [ 27 ], may have unintended public health-related consequences for the environment, animals, and humans [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that other feeding and health management strategies including environmental conditions could have shaped the pattern of expression of both body weight and body weight gain as well as the mortality rate of the birds ( Silveira et al, 2014 ; Nakkazi et al, 2015 ; El-Sabrout et al, 2022 ). Also, within the smallholder poultry production system in Nigeria, farmers’ use of antibiotics is primarily for therapeutic purposes, and not growth promotion ( Bamidele et al, 2022a ). This study did not assess if farmers administering antibiotics observed the required withdrawal period prior to sale ( Turcotte et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%